2021
DOI: 10.1017/jfm.2021.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-range Coulomb repulsion on adhesive particle agglomeration in homogeneous isotropic turbulence

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…In addition to neutral particles, particles in nature could easily get charged after moving through ionized air (Marshall & Li 2014;van Minderhout et al 2021) or encountering collisions (Lee et al 2015). The resulting electrostatic interaction could significantly modulate the fundamental particle dynamics in turbulence, such as clustering, dispersion and agglomeration (Karnik & Shrimpton 2012;Yao & Capecelatro 2018;Ruan, Chen & Li 2021;Boutsikakis, Fede & Simonin 2022;Zhang, Cui & Zheng 2023). For identically charged particles, it has been shown that the Coulomb repulsion could effectively repel close particle pairs and mitigate particle clustering.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to neutral particles, particles in nature could easily get charged after moving through ionized air (Marshall & Li 2014;van Minderhout et al 2021) or encountering collisions (Lee et al 2015). The resulting electrostatic interaction could significantly modulate the fundamental particle dynamics in turbulence, such as clustering, dispersion and agglomeration (Karnik & Shrimpton 2012;Yao & Capecelatro 2018;Ruan, Chen & Li 2021;Boutsikakis, Fede & Simonin 2022;Zhang, Cui & Zheng 2023). For identically charged particles, it has been shown that the Coulomb repulsion could effectively repel close particle pairs and mitigate particle clustering.…”
Section: Introductionmentioning
confidence: 99%